APOLIPOPROTEIN B100 AND SOME LIPID COMPONENTS DURING TRANSITION PERIOD IN COWS UNDER HOT AND THERMONEUTRAL ENVIRONMENTAL CONDITIONS - Fatma Edrees Ibrahim Teama (Journal of Animal and Plant Sciences, 2016)
Study conducted to investigate the biochemical changes in the blood (apolipoprotein B100 and some lipid components) of crossbred cows (Brown Swiss × Baladi) during the transition period under hot and thermoneutral environments. Twelve cows were divided in to two equal groups; hot and thermoneutral environment. Blood samples were collected and ApoB100, total protein, glucose, cholesterol, triglycerides, non-esterified fatty acid (NEFA), β-hydroxybutyric acid (BHBA), and thyroid hormones (T3 and T4) were estimated. Temperature-humidity index as well as milk yield and composition were also recorded in each season. The levels of almost all of studied parameters including ApoB100, total protein, cholesterol, triglycerides, glucose, and thyroid hormones detected in the thermoneutral group significantly exceeded those detected in the other group (hot environment). On the other hand, the levels of NEFA and BHBA detected in the blood of the cows in the hot environment group significantly increased than those of the thermoneutral group. In addition, the blood contents of the two lipid components (NEFA and BHBA) were negatively correlated with the level of ApoB100. Milk yield and composition were also among the parameters affected negatively by heat stress, and were positively correlated with the level of ApoB100 postpartum. The studied parameters may present a valuable assess for the prediction of the disturbance during this critical period.
Keywords: ApoB100; hot environment; transition period; crossbred cows